IMPROVING MEDICATION ADHERENCE IN CHILDREN WITH CF—WHAT A PHARMACIST CAN DO. Issue 8 (11th July 2014) - Christiansen, N; Gohil, J; Lo, A; Bishop, S
Abstract : Aim: The study aimed to explore the factors affecting medication adherence in paediatric cystic fibrosis (CF) patients and to obtain patient opinions on pharmacist-led interventions to improve adherence. Method: Seventeen children aged 11–16 years were eligible to take part in a cross-sectional, self report questionnaire study. The adherence to each treatment option (pancreatic enzymes, inhaled medication and vitamin supplementation) was described on a four point likert scale and additional questions were asked assessing the reason for non-adherence as well as the children's perception of the necessity of the medication. The second section used open and closed questions to assess the potential pharmacist-led interventions the children would perceive to improve adherence. Results: Twelve patients between 12–16 years took part in the study. Adherence rate for pancreatic enzymes (81.8%) was higher compared to inhaled medication (63.7%) and only seven patients (58.3%) took pancreatic enzymes with all meals and snacks. The most common reasons for not taking medications were forgetfulness and taste of medications. The majority of children found it necessary to take pancreatic enzymes (75.0%) and inhaled medication (66.7%), but only 50.0% of children perceived vitamin supplements as necessary. Different pharmacist-led interventions to improve adherence were assessed. When asked about ways of reminding them to take their medication seven (58.3%) children reported that a 'pill box' would help them, three (25%) felt a reminder chart would be useful and two (16.7%) stated that none would help. Information provision on new medication in the CF clinic is predominantly led by the doctors, with eight (66.7%) of the children reporting that doctors explain 'the dose' and some reported 'doctors explains but not in detail'. Four (33.3%) children had not been given information about the new medication. When asked about what way of providing medication information would be most useful five (41.7%) stated medicines information leaflet, 3 (25%) children preferred a CD-ROM with the information and 4 (33.3%) felt that information provision would not help at all. Lastly children were asked whether having a pharmacist attending CF clinics would help and explain their answer. Six (50%) children reported that 'it would not make any difference' and six (50%) reported 'it would help in providing more information about CF medications'. Conclusion: This study has provided unique information on interventions favoured by the children. This can be implemented by the pharmacist with the aim to improve adherence to medication in this patient group.